Plan de Marketing para la Luciérnaga Gifts (2023)
A marketing plan for a company is a tool that is responsible for drawing and implementing concise objectives in order to meet them and make the company more competitive. This marketing plan seeks to project activities for the Firefly Gifs, thinking about the application of marketing Mix of goods and services On- line and in the search that these are recognized by consumers, to expand their market segment that accesses you to enjoy a good reception of your products and services in the city, to comply with the profitability and profits that are sought to be obtained.